Children's perception of national identity and in-group/out-group attitudes: Turkish-Cypriot school children - Mertan, Biran (Psychology Press, 2011)
The aim of the current study was to explore the conceptual development of national identity in Turkish-Cypriot school children ranging from age 6 to 12. Cyprus presents a unique opportunity for the investigation of national identity and related issues due to its vibrant and unresolved political and historical milieu. Currently, there is no comprehensive developmental model that incorporates the conceptual development of national identity in children raised in stable political and national versus unstable political and national scenes. One would expect the sociopolitical environment in Cyprus to shape national identities that include large distances and enmities between the self and the other. In total, 71 Turkish-Cypriot school children responded to the items of the National Identification Scale and were requested to indicate their liking for in-group and out-group targets as well as the appropriateness of traits to describe the in-group and out-groups. In order to provide bases for comparisons between the in-group (Turkish Cypriots) and the enemy out-group (Greek Cypriots), two neutral out-groups (Ireland and the Netherlands) were also used as target groups. The present data suggest that while age has no impact, gender does have an impact on the development of national identity. In the current sample girls demonstrated higher national identity than boys. Data also indicated strong in-group favouritism and negativity towards the enemy out-group.
Keywords: Turkish-Cypriot children; National identity; Political and historical milieu; Conceptual development